Manajemen Kesiswaan Dalam Peningkatan Mutu Lulusan Siswa - Siti Roudhotul Jannah; Nur ‘Azah (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2023)
The objective of the research is to describe the new student admission design, the student support model for improving the quality of graduates, the student leadership assessment in improving graduate quality, and the supportive and inhibitory factors in enhancing high school graduates. Wahid Hasyim. The research method used is qualitative with the type of case study, whereas the data collection techniques used are interviews, observations, and documentation. The data obtained is then analyzed using qualitatively descriptive methods, namely on-going data presentation and data reduction conclusions. The results of this study show that 1) the planning of enrollment activities, in particular the new enrollment model, to improve the quality of graduates requires a new registration policy and admissions criteria and methods of admission of new students. 2) The model of student learning training through extracurricular activities needs more attention to make training activities deepen and expand knowledge. 3) Assessing student quality in written and oral assessment processes with daily repetitions, repetitions of practice, and repetition of semesters 4) Supporting factors for student development are the entire organizational structure that supports student management activities, adequate facilities, communication, and cooperation with students and other organizations.